Initial development of the Stress Monitoring and Response Tool (SMART): A holistic measure of stress following trauma - Emily G. Lowery-Gionta; Haley Stritzel; Liana M. Matson; Meredith A. Bucher; Xinming An; Yinyao Ji; Qinghua Li; Samuel A. McLean; Amy B. Adler (PLoS ONE, 2025)
In the immediate aftermath of trauma exposure, individuals may experience an acute stress reaction (ASR). ASRs may be transient but for individuals operating in high-stakes occupations, these reactions can potentially endanger themselves and those around them. Thus, a better understanding of ASRs could facilitate development of early interventions that help prevent longer-term sequelae. Although existing measures (e.g., PCL-5, CAPS-5) target symptoms that occur in the weeks following trauma, they do not encompass the range of ASR symptoms identified in emerging research. Using data from a large-scale study conducted across emergency departments in the United States, we employed confirmatory factor analysis to identify survey items that sensitively assess ASR symptoms during the peri- and post-trauma phases. These analyses identified 23 core items that are appropriate for administration both immediately following trauma exposure and at later timepoints, as well as 11 supplementary items that can be added to the core items for assessment at later timepoints. Collectively, these items constitute the Stress Monitoring and Response Tool (SMART). Both the SMART Core Scale and the combined SMART Core Scale with Supplemental Items demonstrate good convergent and concurrent validity with several other measures of mental health, physical health, somatic symptoms, pain, and functioning. In addition, the SMART scale remains moderately-to-strongly correlated with multiple measures of symptoms and functional impairment at three months post-trauma. Consequently, the SMART can be used to assess individuals in clinical settings, predict trajectories of recovery, and inform tailoring of interventions across time. Future studies should be conducted to assess the potential utility of the SMART as a decision aid in high-intensity occupational contexts.